Karakteristik Wacana Keilmuan Islam: Suatu Telaah Komparatif - Arditya Prayogi (Universitas Pahlawan Tuanku Tambusai, 2022)
This article focuses on the description of the development of scientific discourse in the Islamic world. The basic principle in Islamic teachings related to science is that there is actually no separation/dichotomy between sciences. However, in its development, science develops and is classified into various types as it is today. This article was written with a qualitative descriptive approach supported by library data. From the results of the study, it can be concluded that scientific discourse in Islam continues to develop and is colored by various scientific discourses. This is increasingly dynamic when the influence of Islam has begun to expand and increasingly offers new discourse dynamics. Keywords: Science, Islam, Development, Knowledge